2015
DOI: 10.1590/1517-869220152105113281
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training & beta-hydroxy-beta-methylbutyrate supplementation on hormones

Abstract: RESUMOIntroduction: In recent years, there was an increased interest on the effects of beta-hydroxy-beta-methylbutyrate (HMB) supplementation on skeletal muscle due to its anti-catabolic effects. Objectives: To investigate the effect of HMB supplementation on body composition, muscular strength and anabolic-catabolic hormones after resistance training. Methods: Twenty amateur male athletes were randomly assigned to supplement and control groups in a double-blind crossover design and participated in four weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…Changes in the resting GH, IGF-1 and TEST concentrations during resistance training have been inconsistent in men. On the other hand, elevated resting GH, IGF-1 and TEST concentrations have been reported in some studies [ 4 , 7 , 31 ], whereas several studies have shown no differences [ 32 , 33 ] or reductions [ 34 ]. To our knowledge, this was the first study that examined the effects of chronic HMB-FA supplementation on hormonal adaptations after resistance training; however, in an earlier study by Townsend et al [ 10 ], enhancement of GH and IGF-1 occurred only by acute ingestion of 1 g HMB-FA prior to a session of resistance exercise.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Changes in the resting GH, IGF-1 and TEST concentrations during resistance training have been inconsistent in men. On the other hand, elevated resting GH, IGF-1 and TEST concentrations have been reported in some studies [ 4 , 7 , 31 ], whereas several studies have shown no differences [ 32 , 33 ] or reductions [ 34 ]. To our knowledge, this was the first study that examined the effects of chronic HMB-FA supplementation on hormonal adaptations after resistance training; however, in an earlier study by Townsend et al [ 10 ], enhancement of GH and IGF-1 occurred only by acute ingestion of 1 g HMB-FA prior to a session of resistance exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, amino acid supplementation can promote adaptations to resistance training via several mechanisms (e.g., promoting protein synthesis, attenuating muscle damage and hormone adaptations) [ 6 ]. Because of the critical role of amino acids, recent studies have investigated the efficacy of β-Hydroxy-β-methylbutyrate (HMB) supplementation for promoting resistance exercise adaptations [ 7 , 8 ]. HMB is a metabolite of the amino acid leucine, a potent stimulus of translation initiation and protein synthesis [ 8 ], and several studies indicated that HMB could enhance muscle size and strength performance [ 7 , 9 ], elevate anabolic hormones [ 10 ] and attenuate catabolic hormones [ 11 ] following resistance exercise.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations